Related Video

Let `f : R to R : f(x) =(1)/(2) (3x+1) ` .Show that f is invertible and find `f^(-1)`

27.7 K+ Views | 1.4 K+ Likes

Let `f: R->R` be defined by `f(x)=3x-7` . Show that `f` is invertible and hence find `f^(-1)` .

67.5 K+ Views | 53.4 K+ Likes

3.8 K+ Views | 100+ Likes

Show that `f: RrarrR` defined by `f(x) = (3x-1)/2, x in R` is invertible function and find `f^-1`.

1.5 K+ Views | 76 Likes

Let `f : R rarr R` be defined as `f(x)=2x+3`. Show that f is invertible and find `f^-1 : R rarr R`.

20.0 K+ Views | 1.0 K+ Likes

Let `f: R to R : f (x) = 4x+3 ` for all `x in R` . Show that f is invertible and find `f^(-1)`

21.2 K+ Views | 1.1 K+ Likes

If `f:R rarr R` and `f(x)=(3x+6)/8` then show that `f` is invertible and find `f^(-1)`

6.3 K+ Views | 400+ Likes

Let f: `R to R` be defined by `f(x) = 3x + 4, X in R` Is f invertible ? If so, give a formula for `f^(-1)`.

900+ Views | 49 Likes

Let `f : Q to Q : f(x) =3x -4` show tha t f is invertible and find `f^(-1)`

17.2 K+ Views | 800+ Likes

Show that `f: R-{-1}->R-{1}` given by `f(x)=x/(x+1)` is invertible. Also, find `f^(-1)` .

5.5 K+ Views | 1.4 K+ Likes

80.6 K+ Views | 4.0 K+ Likes

Let `R^(+) ` be the set of all positive real numbers. Let <br> `f : R^(+) to R^(+) : f(x) =e^(x) ` for all `x in R^(+)` . Show that f is invertible and hence find `f^(-1)`

44.3 K+ Views | 2.2 K+ Likes

Let `f : R rarr R : f(x) = (2x-3)/(4)` be an invertible function. Find `f^(-1)`.

3.0 K+ Views | 100+ Likes

Let `f : R to R : f(x) =(2x-7)/(4)` be an invertible function . Find `f^(-1)`

41.8 K+ Views | 28.2 K+ Likes

400+ Views | 22 Likes

show that the function `f : R to R : f (x) =2x +3` is invertible and find `f^(-1)`

28.3 K+ Views | 1.4 K+ Likes

Show that `f:R - {1} to R - {1}` given by `f(x) = (x)/(x + 1)` is invertible. Also, find `f^(-1)`.

4.6 K+ Views | 200+ Likes

3.9 K+ Views | 3.3 K+ Likes

`f : R to R` be defined as `f(x) = 4x + 5 AA x in R` show that f is invertible and find `f^(-1)`.

1.4 K+ Views | 400+ Likes

Show that `f : R-{a} rarr R-{-1}` defined by `f(x)= (a+x)/(a-x)` is invertible. Find the formula for `f^-1(x)`.

500+ Views | 26 Likes